PEMBUATAN LKPD BERBASIS INKUIRI TERBIMBING MATERI UNSUR DAN SENYAWA UNTUK SISWA SMPN 2 SUNGAI RAYA - Theresia, Monica; Sahputra, Rachmat; Muharini, Rini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the feasibility level of guided inquiry-based LKPD on elemental and compound materia,l and the readability level of guided inquiry-based LKPD on elemental and compound material. The form of research used was research and development (R & D) that adopted from Sugiyono's development. The subject of this study was guided inquiry-based LKPD which was tested on VIIC class students at SMP Negeri 2 Sungai Raya by taking 32 students. The data collection technique used was questionnaires. The data collection instrument used is the feasibility sheet and readability questionnaire. The data processing technique used was the feasibility assessment of LKPD based on guided inquiry and readability of the LKPD. The results of data processing showed that the developed LKPD had a very valid feasibility level on content eligibility (95.11%), strongly valid in presentation feasibility (89.33%), quite valid in linguistic feasibility (78.67%), and quite valid on the feasibility of graphics (77.22%). The readability test results for students on the products obtained responses of students with an average score of 83.76% with interpretations, which was classified as quite valid. Thus, inquiry-based LKPD guided by material elements and compounds was suitable for using in the learning process.Keywords:Â Elements and compound, feasibility, LKPD based on guided inquiry, and student response.